Systematic review of the ergometric effect of caffeine (Research, Society and Development, 2023)
Caffeine is a stimulating substance found in certain plants, which helps in sports in improving the athlete's performance. The incentive in the scientific branch for research is essential to understand the benefits and harms of this resource for users, studies that aim to track and detect measures that mitigate the fatigue of athletes are essential to increase their competitive performance. Thus, the present research aimed to investigate the relationship between the ergogenic effect of caffeine and the impact on the practice of physical exercise. For this, a systematic review of its effects was carried out, using the Scielo and Pubmed databases. Therefore, in the systematic search, 433 articles were found, which were filtered with exclusion and inclusion criteria, converting to an amount of 8 articles. Finally, the effectiveness of caffeine as a potent ergogenic that delays parasympathetic stimulation, heart rate recovery, but mainly capable of producing improvements in muscle endurance in different sports has been identified in several works.